ACTIVATED CARBON-BASED TREATMENT AS AN ALTERNATIVE SOLUTION FOR BATIK WASTEWATER POLLUTION IN TANJUNG BUMI, MADURA - Yunin Hidayati; Ginta Siahaan (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
The vast majority the batik industry produces batik waste containing synthetic dyes that is harmful to the environment. The batik industry is expanding in Indonesia and has an impact on economic growth and socio- cultural development. However, the development of batik industry also increases waste that has a detrimental impact on the environment, resulting in pollution. This also occurred in Tanjung Bumi, one of the centers of the batik industry on the island of Madura, Indonesia. This study aims to find an alternative technology for processing batik waste containing synthetic dyes. The use of activated carbon which is easy to obtain, cheap, simple and effective in decomposing waste is projected to be an alternative, for craftsmen, to process batik waste. The results of the Cr content test showed that there was a decrease in Cr levels in batik wastewater after being given activated carbon; there was a reduction in Cr levels up to 30.83 g/L after giving activated carbon with various concentrations for 21 days. In addition, there was also a significant decrease in the conductivity value of batik waste after being treated with activated carbon. These results indicate that activated carbon can be used as an alternative for batik wastewater treatment. However, to get more optimal results, the use of activated carbon for handling wastewater needs combination with other methods.